Sistem Informasi Geografis Pemetaan Hasil Penjualan Sales Lapangan Dengan Leaflet.js dan OpenStreetMap - Putu Novendra Krisna Wiharadhita; I Gede Putu Krisna Juliharta; I Gede Juliana Eka Putra (Jurnal Tekno Kompak, 2023)
Maps have become part of human life along with the development of technology and information. In the digital era, paper-based maps are slowly being shifted since the advent of the internet, with the emergence of online mapping platforms. The use of this map is increasingly relevant to the existence of a Geographic Information System. Geographic Information System is one of the main needs of various organizations. By using a Geographic Information System, a data can be displayed in real terms with a geographical map as the basis, where various business fields will use it, for example, the sales of a service. PT ICON+ in the Bali and Nusra regions uses field sales to make sales, and the final sales results are carried out manually via the WhatsApp application in a group chat, which is ineffective due to the large number of messages in one group chat. In its development, researchers use a number of frameworks and libraries to develop this geographic information system. For developing this Geographic Information System, Laravel is used, which is a PHP framework for building a web-based system. Another library, leaflet.js also used for building an interactive mapping system that uses OpenStreetMap as a map used by the system. The application development cycle uses a framework named Scrum, which is effective in developing a software within a certain deadline. The final result of this research, produces a Geographic Information System that is able to map the Internet service network of the company PT. ICON+ and the amount of sales made based on the service network pole, data on the network service cluster mapping, and data export features.